THE INFLUENCE OF PROFESSIONAL ETHICS, EMOTIONAL INTELLIGENCE AND PROFESSIONALISM ON THE DECISION MAKING OF GIVING AUDITOR OPINION: (Case Study at KAP Registered in the Ministry of Finance and Located in Tangerang City) - Maryati; Jelanti, Desi (Transpublika Publisher, 2023)
In the current business landscape, the credibility of financial reporting relies heavily on the integrity of auditors and their decision-making processes. This study aims to examine and analyze about the effect of professional ethics, emotional intelligence and professionalism on the decision making of giving auditor opinion. The type of research used in this study is multiple linear regression analysis. The research was conducted using primary data obtained through distributing questionnaires to independent auditors who work at Public Accounting Firms registered with the Ministry of Finance and having an address in Tangerang City. The sampling method in this study used convenience sampling with the sample result obtained in this study as many as 4 Public Accounting Firms. Data analyze using descriptive statistics, classical assumption test and hypothesis testing. Based on the testing result was found professional ethics, emotional intelligence and professionalism simultaneously influence the decision making of giving auditor opinion. Calculation of R2 yields 75,4%, it means there are 24,6% who explain by other variables outside this study. Based on the partial test result, it was found independent variable (professional ethics, emotional intelligence and professionalism) had an effect on the dependent variable, the decision making of giving auditor opinion.